Integrating Communities into REDD+ in Indonesia - Jurgens, Emile; Kornexl, Werner; Oliver, Chloe; Gumartini, Tini; Brown, Tim (PROFOR, Washington, DC, 2013)
The Government of Indonesia (GOI) is in the process of designing a national REDD+ mechanism to allow it to access donor funding in the medium term, and funding from a potential performance based mechanism in the long term. This policy brief is focused on the broad question of how REDD+ can address underlying community issues such as lack of access to forest land, and does not deal with the more specific questions of legal and institutional frameworks for such a mechanism. More specifically, the brief highlights the need and opportunity for integrating community development approaches into a REDD+ framework. The brief is based largely on a review of literature on Payments for Ecosystem Services (PES) programs, on interviews with a number of representatives from Indonesian small grants programs, and on discussions with the team that is involved in the implementation of PNPM programs at the World Bank Office in Jakarta. Indonesia is a major Green House Gas (GHG) emitter (about 2.1 gigatons of carbon dioxide equivalent in 2005) and most of the emissions come from deforestation and peatland degradation. Indonesia has approximately 94 million hectares of natural and planted forests, representing around 52 percent of its total land area. The Ministry of environment estimates that in 2000, as much as 60 percent of Indonesia's total GHG emissions were due to land use changes, including deforestation, forest degradation and peat loss. In recent years, REDD+ has become a focus of policy development in Indonesia. The Forestry Research and Development Agency (FORDA) took the lead in 2007 by forming the Indonesia Forest Climate Alliance (IFCA) to articulate a national approach in response to shifting opportunities emerging from international negotiations on climate action and financing.